1990
DOI: 10.1093/nar/18.13.3953
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of single-base and triple-base changes in the integrase arm-type binding sites on the site-specific recombination of bacteriophage lambda

Abstract: Triple-base changes were made in each of the five Integrase (Int) arm-type binding sites of bacteriophage lambda. These triple changes, called ten mutants, were compared with single-base changes (hen mutants) for their effects on integrative and excisive recombination. The presence of ten or hen mutations in the P1, P'2, or P'3 sites inhibited integration, but the ten P'3 mutant was 10-fold more defective than the analogous hen mutant. The results with these mutants suggest that the P1, P'2, P'3, and possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 27 publications
8
63
0
Order By: Relevance
“…Int binding at N-domain sites is abolished by changing the conserved central 3 bases of the consensus recognition sequence from TCA to GTC (Fig. 3A) (16). The phenotypes of these ''ten'' mutants were consistent with earlier deletion studies (21,22) and showed that the P1 but not the P2 site is required for integrative recombination.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Int binding at N-domain sites is abolished by changing the conserved central 3 bases of the consensus recognition sequence from TCA to GTC (Fig. 3A) (16). The phenotypes of these ''ten'' mutants were consistent with earlier deletion studies (21,22) and showed that the P1 but not the P2 site is required for integrative recombination.…”
Section: Resultssupporting
confidence: 86%
“…3C, the PЈ3 arm-type site, which is not required for excisive recombination, also carries a ten mutation. We used this configuration because in the excisive reaction a ten mutation in PЈ3 enhances the dependence on the P2 site (16,23). Indeed, when the PЈ3 arm-type site is restored to wild type in the lotL by lotR reaction, the dependence on the P2 arm-type site is less pronounced (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 incorporate the findings reported here, such as the clockwise directionality of the arm sites, the counterclockwise flipping-out of the N-terminal domains, and the arm DNA crossing of the Ex strands, as well as older findings, such as the differential accessory-site usage in excision versus integration (16,39,40) and the antiparallel orientation of arm sites in the P and PЈ arms (17). Because only three arm sites are used either in excision or integration (14,16), the models are drawn with one of the N-terminal Int domains bound nonspecifically to DNA sequences adjacent either to the P2 or the P1 sites for excision or integration, respectively. Consistent with this feature of the models is the finding that Int can form ternary two-arm HJ complexes in which one arm DNA contains two arm sites, whereas the other contains one arm site plus a potential nonspecific binding site (17).…”
Section: Discussionmentioning
confidence: 78%
“…Here, the five arm-type Int binding sites and the six sites for the accessory DNA bending proteins are encoded. Two overlapping subsets of this ensemble are used for integrative and excisive recombination (15,16), as indicated by the differential color coding in Fig. 1 A.…”
mentioning
confidence: 99%